Static knee alignment measurements among Caucasians and African-Americans: The Johnston County Osteoarthritis Project - Nelson, Amanda E. (2009)
OBJECTIVE: To determine if knee alignment measures differ between African Americans and Caucasians without radiographic knee osteoarthritis (rOA). METHODS: A single knee was randomly selected from 175 participants in the Johnston County Osteoarthritis Project without rOA in either knee. Anatomic axis, condylar, tibial plateau, and condylar plateau angles were measured by one radiologist; means were compared and adjusted for age and body mass index (BMI). RESULTS: There were no significant differences in knee alignment measurements between Caucasians and AfrAm among men or women. CONCLUSIONS: Observed differences in knee rOA occurrence between AfrAm and Caucasians are not explained by differences in static knee alignment.